(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2017)
The Dictionary of Synonyms in Macedonian language by Tole Belchev and Snezana Venovska-Antevska was published in 2017. This Dictionary consists 583 pages of synonyms text, a preface and information about the book, a list of abbreviations and used and consulted literature. In the key part of the Dictionary 19,365 initial words are presented in an alphabetical order. It is important to mention that there are more than 50,000 words in the Dictionary, since most initial words have more than one synonym. The word processing in the Dictionary first had started in two directions. One is to state the archaisms, and the other is to state neologisms. The authors have paid attention to include words that are used with translational meaning associated with the initial word, but also to display a lexeme that is used in Macedonian language. As synonyms of the initial words, the authors display words with the same meaning, similar meaning, but also words that have developed synonyms along an associative path, that are deeply rooted in Macedonian language.